Perancangan Arsitektur Sistem Informasi di MA Al Hidayah Menggunakan Metode EAP - Nugraha, Muhamad Fahmi; Yanti, Lina Dwi (Ma'soem University, 2025)
The advancement of information technology requires educational institutions to manage data and business processes more efficiently and in an integrated manner. MA Al Hidayah, as a private Islamic senior high school, faces challenges in handling academic and administrative data, which are still mostly managed manually and lack integration. This study aims to design an information system architecture using the Enterprise Architecture Planning (EAP) method as a solution to support the institution’s vision, mission, and operational needs. The EAP approach consists of four layers: planning initiation, current business and system modeling, architecture design (data, application, and technology), and implementation and migration planning. The results of this study include a blueprint for data, application, and technology architecture, along with implementation strategies and human resource requirements. The proposed architecture is expected to serve as a guide in building an integrated information system that enhances operational efficiency, information transparency, and data-driven decision-making at MA Al Hidayah.